2023
DOI: 10.3390/plants12142587
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Calcium Absorption by Tomato Plants: Comparing the Effects of Calcium Sources and Adjuvant Usage

Eduardo Santos,
Gabriel Sgarbiero Montanha,
Luís Fernando Agostinho
et al.

Abstract: The deficiency of calcium (Ca) reduces the quality and shelf life of fruits. In this scenario, although foliar spraying of Ca2+ has been used, altogether with soil fertilization, as an alternative to prevent deficiencies, little is known regarding its absorption dynamics by plant leaves. Herein, in vivo microprobe X-ray fluorescence was employed aiming to monitor the foliar absorption of CaCl2, Ca-citrate complex, and Ca3(PO4)2 nanoparticles with and without using adjuvant. We also investigated whether Sr2+ ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Previous studies conducted using either synchrotron or benchtop-based XRF setups revealed elemental doses of between 10 2 and 10 4 Gy. , As detailed in Figure S7C, one should notice that a minimum 50 h exposure would be required to achieve such doses in this current setup. Since in vivo XRF measurements usually encompass a few seconds up to a dozen minutes, ,, there is no evidence that X-ray-induced radiation damage might be an issue for the SIPA setup.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies conducted using either synchrotron or benchtop-based XRF setups revealed elemental doses of between 10 2 and 10 4 Gy. , As detailed in Figure S7C, one should notice that a minimum 50 h exposure would be required to achieve such doses in this current setup. Since in vivo XRF measurements usually encompass a few seconds up to a dozen minutes, ,, there is no evidence that X-ray-induced radiation damage might be an issue for the SIPA setup.…”
Section: Resultsmentioning
confidence: 99%
“…Investigating the absorption and transport of minerals by roots and leaves is crucial for nutrition studies, as it provides a mechanistic understanding of the dynamics of mineral absorption and transport processes and ultimately fosters novel strategies toward higher nutrient use efficiency. ,,, Although it can also be evaluated using other analytical techniques, such as ICP OES and ICP-MS, , these do not enable in vivo studies, while the latter involves complex radiolabeled materials acquisition and safety . Hence, XRF exhibits unique features for evaluating the absorption and transport of minerals across plant tissues on a real-time basis. ,,,, Considering foliar absorption, SIPA provides an accurate in vivo assessment of the absorption and transport processes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations